“Vidas negras importam” para a formação em direito? : a educação das relações étnico-raciais no curso de Direito da UFS e nas escolas das carreiras jurídicas de Sergipe - Jesus, Alexis Magnum Azevedo de (2023)
The work analyzes the education of ethnic-racial relations in the law course at UFS and in the schools of legal careers in Sergipe - EJUSE, ESMPSE and ACADEPOL - in the face of the genocide of the black population. The concepts of genocide of the black population, law, education of ethnic-racial relations and curriculum are discussed, as well as the socio-historical development of Law courses, with emphasis on black insurgencies in this context. The work has Marxism as its theoretical-methodological reference, which understands as indispensable the articulation of the black university intelligentsia with the knowledge of the historical struggle of the black movement. In this way, making use of political denouncements by black organizations, the contribution of hip-hop, bibliographic review, documental analysis of curricula and semi-structured interviews with course coordinators, the research concludes that the education of ethnic-racial relations has a very low insertion in legal education in Sergipe, which directly contributes to the deepening of the genocide of the black population.